Criminal Liability of Corporations for Worker Supervision Practices Outside Working Hours from the Perspective of Labor Law, Ite Law, and Personal Data Protection - Handono, Totok; Humulhaer, Siti; Azhari, Muhammad Rizki; Sudhana, Harry; Rahayu, Dewi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The expansion of digital technology has enabled corporations to conduct employee surveillance beyond working hours through electronic systems and personal data monitoring. Such practices raise legal concerns as they may exceed employer authority under labor law and violate personal data protection principles. This study analyzes the legal limits of off-duty employee surveillance based on Indonesian labor law, electronic information law, and personal data protection law, and formulates corporate criminal liability for such practices. Using normative juridical methods and statutory analysis, the study finds that off-duty surveillance lacks legal basis in labor law, may constitute unlawful electronic access under electronic information law, and represents unlawful personal data processing under data protection law. When implemented as corporate policy, such surveillance fulfills elements of corporate criminal liability. Off-duty employee surveillance constitutes a deviation from statutory limits of corporate authority and infringes workers’ privacy rights.